E-Learning Teaching: Supportive Online Course ‘English Fastpass’ - Ilona Kostikova; Svitlana Miasoiedova (Educational Challenges, 2022)
The aim of this paper is to prove the hypothesis that in order to cope with the adversities and hardships and meet the demands of the wartime and pandemic challenges, a complex of tools and techniques has to be applied including new teaching strategies with the use of multimedia, mobile applications and employing learning possibilities of social networking sites, Google classroom tools and other instruments with online course “English Fastpass”.